2020
DOI: 10.1093/cercor/bhaa168
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting-State Functional Connectivity Between Awake and Isoflurane Anesthetized Marmosets

Abstract: The common marmoset (Callithrix jacchus) is a New World primate that is becoming increasingly popular as a preclinical model. To assess functional connectivity (FC) across the marmoset brain, resting-state functional MRI (RS-fMRI) is often performed under isoflurane anesthesia to avoid the effects of motion, physiological stress, and training requirements. In marmosets, however, it remains unclear how isoflurane anesthesia affects patterns of FC. Here, we investigated the effects of isoflurane on FC when deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 76 publications
8
52
0
Order By: Relevance
“…These RSNs were thresholded at z = 2.3 for visual purposes. Obtained RSNs were consistent with previously observed networks in marmosets (Belcher et al, 2013; Ghahremani et al, 2016; Hori et al, 2020b) such as default mode network (DMN) (Fig. 1A), attention network (ATN) (Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These RSNs were thresholded at z = 2.3 for visual purposes. Obtained RSNs were consistent with previously observed networks in marmosets (Belcher et al, 2013; Ghahremani et al, 2016; Hori et al, 2020b) such as default mode network (DMN) (Fig. 1A), attention network (ATN) (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Fourteen components identified as resting-state networks in the marmosets. These networks were labeled based on previous studies (Belcher et al, 2013; Hori et al, 2020b) as follows: (A) default mode network (DMN); (B) attention network (ATN); (C) salience network (SAN); (D) left primary visual network (pVIS-Lt); (E) right primary VIS (pVIS-Rt); (F) orbitofrontal network (ORN); (G)-(J) high-order VIS (hVIS1-4); (K)-(M) somatomotor networks ventral (SMNv), dorsal (SMNd), and medial (SMNm); (N) premotor network (PMN). Color bar represents the z-score of these correlation patterns thresholding at 2.3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional interactions between distributed brain areas within specific neural networks give rise to coherent patterns of hemodynamic signals, measured as BOLD activity. Covariant relations of spontaneous BOLD signals in the resting state have been reported in humans ( Arcaro et al, 2015a ; Biswal et al, 1995 ; Fox et al, 2009 ; Power et al, 2011 ; Sporns and Honey, 2013 ) and awake NHPs ( Belcher et al, 2016 ; Ghahremani et al, 2017 ; Hori et al, 2020a ; Leopold et al, 2003 ; Liu et al, 2013 ; Logothetis, 2003b ; Silva, 2017 ; Wang et al, 2012 ) as well as in anesthetized NHPs ( Hori et al, 2020a , b ; Hutchison et al, 2012 ; Hutchison et al, 2013 ; Mantini et al, 2012a ; Vincent et al, 2007 ; Wu et al, 2016 ; Wu et al, 2017 ; Zhang et al, 2019 ). These studies have revealed that specialized cognitive and sensory networks retain their basic functional connectivity, even when not specifically engaged in task-relevant operations.…”
Section: Non-invasive Imaging Methods Are Used In Experimental and CLmentioning
confidence: 88%
“…Functional magnetic resonance imaging (fMRI) plays an important role in identifying the functional architecture of marmoset cortex (Belcher et al, 2013;Hori et al, 2020a;Schaeffer et al, 2019c) and in establishing brain homologies between primate species (Ghahremani et al, 2016;Hori et al, 2020b;Schaeffer et al, 2019c). In particular resting-state fMRI has been used (i) to identify homologous large-scale brain networks between marmosets and humans (Ghahremani et al, 2016;Hori et al, 2020a;Schaeffer et al, 2019c), (ii) to define functional boundaries based on intrinsic functional connectivity (Schaeffer et al, 2019b(Schaeffer et al, , 2019a, and (iii) to use functional connectivity "fingerprints" of brain areas to establish homologies between marmosets, rodents, and humans (Schaeffer et al, 2020a). Because resting state patterns are state-agnostic and spontaneous, however, this technique cannot be used to map the functional correspondences of interspecies BOLD fluctuations over time.…”
Section: Introductionmentioning
confidence: 99%